1993
DOI: 10.1007/bf02886699
|View full text |Cite
|
Sign up to set email alerts
|

The detection of peripheral venous pulsation using the pulse oximeter as a plethysmograph

Abstract: The pulse oximeter can serve as a sensitive photoelectric plethysmograph in the operating room. It was noted in several cases that the plethysmographic waveform showed a high degree of variability during diastole. Three patients are described with discrete diastolic peaks on the plethysmograph. Further investigation revealed that these diastolic peaks appear to correlate with peripheral venous pulsation, which seems to have a central venous origin. Evidence is presented that the plethysmographic detection of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 10 publications
0
30
0
Order By: Relevance
“…It is well known that the PPG waveform is influenced by both positive pressure ventilation [8] and the peripheral venous pulsations [1,9]. In the case of positive pressure ventilation, we hypothesize that the effect on the PPG waveform is mediated by volume changes in the venous compartment.…”
Section: Measuring Venous Oxygen Saturation Via Physiological Sourcesmentioning
confidence: 79%
See 2 more Smart Citations
“…It is well known that the PPG waveform is influenced by both positive pressure ventilation [8] and the peripheral venous pulsations [1,9]. In the case of positive pressure ventilation, we hypothesize that the effect on the PPG waveform is mediated by volume changes in the venous compartment.…”
Section: Measuring Venous Oxygen Saturation Via Physiological Sourcesmentioning
confidence: 79%
“…The reasoning behind looking at this frequency is as follows. The central venous pulse waveform can be transmitted through the venous system, leading to peripheral venous pulsations and the appearance of a diastolic peak in the PPG signal [1]. When such a diastolic peak is superimposed on the systolic cardiac peak, the overall signal has peaks that occur at twice the cardiac frequency.…”
Section: Respdc and Respac: Respiratory Frequency Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…78,79 Venous oxygenation Multiple authors have described the presence of venous ''interference'' in the PPG signal. 11,80,81 The venous contribution to the PPG signal should not, however, be thought of as interference. Rather, it provides additional information, the utility of which has yet to be fully understood.…”
Section: 6470-72mentioning
confidence: 99%
“…The PPG is also affected by changes in the volume of venous blood in the tissue vasculature. Shelley et al [13] published several case studies that showed small peaks appearing in the diastolic part of the recorded PPG waveforms. These peaks were not present in the arterial pressure waveform but were shown to coincide with peaks in the simultaneously recorded peripheral venous pressure wave.…”
Section: Effect Of Venous Pulsation On the Photoplethysmographic Wavementioning
confidence: 99%